Anionic block copolymer vesicles act as Trojan horses to enable efficient occlusion of guest species into host calcite crystals. Issue 44 (17th September 2018) - Ning, Yin; Whitaker, Daniel J.; Mable, Charlotte J.; Derry, Matthew J.; Penfold, Nicholas J. W.; Kulak, Alexander N.; Green, David C.; Meldrum, Fiona C.; Armes, Steven P.
Abstract : 'Trojan Horse' anionic poly(methacrylic acid)–poly(benzyl methacrylate) vesicles enable efficient incorporation of either nanoparticles or soluble small molecules within calcite. Abstract : We report a versatile 'Trojan Horse' strategy using highly anionic poly(methacrylic acid)–poly(benzyl methacrylate) vesicles to incorporate two types of model payloads, i.e. either silica nanoparticles or an organic dye (fluorescein), within CaCO3 (calcite). Uniform occlusion of silica-loaded vesicles was confirmed by scanning electron microscopy, while thermogravimetry studies indicated extents of vesicle occlusion of up to 9.4% by mass (∼33% by volume). Efficient dye-loaded vesicle occlusion produces highly fluorescent calcite crystals as judged by fluorescence microscopy. In control experiments, silica nanoparticles alone are barely occluded, while only very weakly fluorescent calcite crystals are obtained when using just the fluorescein dye. This new 'Trojan Horse' strategy opens up a generic route for the efficient occlusion of various nanoparticles and organic molecules within inorganic host crystals.